PD1 regulates T cell exhaustion phenotypes and disease aggressiveness in CTCL. (October 2021) - Daniels, Jay; Park, Joonhee; Wartewig, Tim; Martinez-Escala, Maria Estela; Pro, Barbara; Sosman, Jeffrey; Guitart, Joan; Rao, Deepak; Ruland, Jurgen; Choi, Jaehyuk
Abstract : Introduction: Cutaneous T cell lymphomas (CTCLs) are a heterogenous group of lymphomas of the skin-homing CD4+ T cell. Although the median survival for patients with stage IV disease is generally poor, there is significant heterogeneity with some stage-matched patients surviving <6 months while others survive >10 years. Currently, it is unclear why this is the case, and whether there are any biomarkers for patients with the most aggressive forms of disease. To address this knowledge gap, we sought to combine multi-omics and functional assays to a clinically annotated cohort of CTCLs to identify drivers of disease heterogeneity. Materials and methods: To explore the molecular underpinnings of disease heterogeneity in CTCL, we combined whole-genome sequencing, RNA-sequencing, immunophenotyping, and ex vivo proliferation assays on sorted malignant cells from 14 patients with leukemic CTCL. Whole genome sequencing was analyzed for single nucleotide and copy number variants. To determine ex vivo proliferation, sorted malignant cells were stained with carboxyfluorescein succinimidyl ester (CFSE), cultured with T cell receptor stimulation or cytokines and assessed via flow cytometry. Results: Unexpectedly, we observed significant heterogeneity in the ability of malignant CTCL cells to proliferate to T cell receptor and cytokine signals ex vivo. A subset of samples proliferated to more stimuli than healthy controls, another group of samples similarly to controls, and yet another group significantly less. Strikingly, unbiased DNA and RNA-seq analyses revealed a critical role for the co-inhibitory receptor and tumor suppressor PD1. PDCD1 (the gene which encodes PD1) was the most highly expressed gene in samples that failed to proliferate ex vivo compared to those that proliferate highly. The single gene significantly more frequently mutated in highly proliferating samples was PD1. Integrating genomic, transcriptomic, and functional data, we observed that most samples harbored features of T cell exhaustion, including diminished proliferation and effector cytokine production, and expression of markers of T cell exhaustion. However, samples with deletions of PD1 reversed this phenotype. These samples had higher ex vivo proliferation and effector cytokine production, and lower expression of T cell exhaustion markers. Accordingly, samples with deletions of PD1 had significantly worse prognoses in both stage IV disease and in stage II-III MF. Conclusions: By integrating genotype, transcriptome, and functional status, we have identified that a majority of CTCLs harbor features of T cell exhaustion. A subset of CTCLs which harbor PD1 deletions reverse the T cell exhaustion phenotype. Consistent with this, PD1-deleted CTCLs have significantly worse overall survival in stage-matched patients. Our data establishes T cell exhaustion status and PD1 deletions as novel drivers of heterogeneity in cutaneous T cell lymphoma.